Solid pseudopapillary neoplasm–Case report of a rare pancreatic tumor - Branco, Cláudio (Int J Surg Case Rep, 2017)
INTRODUCTION: Solid pseudopapillary neoplasm (SPN) is a rare pancreatic tumor. Most patients are female within the second or third decade of life with only a small minority concerning children. Frequently described as low malignant potential tumors, surgical resection remains the main treatment. PRESENTATION OF CASE: The authors present a case of a SPN diagnosed in a 17-year-old Caucasian girl with vomiting and abdominal pain localized to the right upper quadrant. CT scans and MRI scans showed the presence of a well-defined tumor arising from the pancreatic head with 14 cm of greater diameter. Pylorus-preserving pancreatoduodenectomy was performed and histopathology confirmed a SPN with complete resection and no evidence of malignancy. DISCUSSION: SPN are usually found incidentally hence the importance of an accurate radiologic diagnosis. Symptoms may be present such as abdominal pain or vomiting due to compression, namely in large tumors. A surgical approach is usually indicated aiming complete resection, with tumor size not predicting resectability. CONCLUSION: Solid pseudopapillary tumors of the pancreas are extremely rare and usually have an excellent long-term prognosis after surgical resection.